New features of the morphotropic phase boundary in the PbZrO3-PbTiO3 system: A Raman spectroscopy study - Ayala, A. P.; Lima, KCV; Souza, A. G.; Mendes, J.; Freire, PTC; Guedes, I; Melo, FEA; Araujo, E. B.; Eiras, J. A. (Taylor & Francis Ltd, 2002)
In this work we present a Raman study of PbZr1-xTixO3 ceramics with composition values close to the morphotropic phase boundary region. The analysis of the Raman spectra leads to the determination of the monoclinic phase extension at different temperatures in a very good agreement with those determined by diffraction techniques. Therefore the obtained results show that Raman spectroscopy is a powerful and suitable technique to study structural phase transitions in PbZr1-xTixO3.
Keywords: PZT; phase transitions; Raman spectroscopy